The Efforts of the Cahaya Perempuan WCC NGO in Addressing Cases of Violence Against Women in Dating Relationships - Reza Oktaviani; Heni Nopianti; Diyas Widiyarti (Green Publisher Indonesia, 2024)
Based on Komnas Perempuan's annual records in 2023, from the types of personal violence reported to service institutions, the level of dating violence cases is in the first place with 3,528 cases. According to data obtained from Cahaya Perempuan NGO during 2018-2023, victims of dating violence cases totaled 29 cases. The research aims to describe Cahaya Perempuan's efforts in handling women victims of violence in dating relationships. This research also explores the causes of violence and the reasons why victims report their cases. The research method used is a qualitative method approach with descriptive analysis type. Data collection techniques are in-depth interviews with semi-structured types and documentation studies in the form of statistical data, as well as other supporting data. The selection of informants was carried out by purposive sampling with five informants, namely two active activists of Cahaya Perempuan NGO and three informants of victims of dating violence. Data analysis techniques were carried out with data reduction, data presentation and conclusion drawing. The results showed that the efforts made by Cahaya Perempuan NGO in handling victims of violence against women in dating, namely information services, counseling, and legal consultation through advocates. This form of handling is adjusted to the needs of victims to be legally processed or only counseling or consulting assistance. Cahaya Perempuan NGO provides more handling of dating violence cases in the form of counseling or consulting assistance and information services to victims. Meanwhile, legal consultation efforts through advocates are carried out when victims need legal assistance.